NEW INVESTOR LITERATION PROGRAM SEBAGAI UPAYA PENINGKATAN PENGETAHUAN INVESTASI PASAR MODAL SISWA SMA NEGERI 2 PEMALANG - Muhammad Aris Safii; Versiandika Yudha Pratama; Happy Sista Devy (LPPM Universitas Bina Bangsa, 2022)
Investment essentially investing capital with the hope of getting a profit in the future. One of the investment instruments is the capital market. Financial inclusion index data shows that the capital market literacy index in Indonesia is quite low compared to other financial literacy indexes such as banking, insurance, financing institutions and pawnshops. In fact, investing in the capital market is one investment that is quite easy and profitable. In terms of the age of investors, the age range of 15-17 years, which is the age of teenagers, still has a minimal level of capital market investment literacy. This is also experienced by students of SMA Negeri 2 Pemalang who are still new to capital market investment. The New Investor Literacy Program is expected to be able to increase investment understanding so that students can prepare for financial well-being in the future. The method used in this activity is education and training, where SMA Negeri 2 Pemalang students will be given education in advance about the concept of capital market investment, then continue with training on how to practice investing in capital market products in Indonesia. In general, this activity ran smoothly and conducively with the enthusiasm and curiosity of SMA Negeri 2 Pemalang students who were so great in terms of capital market investment.